Implementasi Metode Tilawati Dalam Meningkatkan Kemampuan Menghafal Al-Qur’an Santri Madrasah Diniyah Darussalam Gresik - Anggraini, Novita; Amirudin, Noor (STIT Muhammadiyah Paciran Lamongan, 2023)
This study aims to determine the implementation of the tilawati method in improving the ability to memorize the al-Qur’an at Madrasah Diniyah Darussalam Gresik. This research method uses descriptive qualitative. The research subjects were the tilawati vol 2 students, each group consisting of 15 students. The researcher made observations of the teacher's activities including the implementation of the opening activities, the implementation of the core activities, the teacher's learning approach, the arrangement of the learning class and the implementation of evaluations, in addition to observing the teacher's activities, the researchers also observed the activities of the students in learning including the students' fluency in reading the al-Qur’an. The results of this study, as a whole are in accordance with the provisions set by the tilawati institution, but there are a number of things that are adjusted and combined with the conditions and programs at Madrasah Diniyah Darussalam Gresik, such as when learning has not been given writing material and supporting materials for memorizing prayers prayer, in a special class an additional method is applied, namely a private method.